Implementation Of Civic-Action Learning Model Based On SDGs To Realize The Political Civility Of The Younger Generation - Bali Widodo; Yogi Nugraha (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2026)
At this time, the political civilization of the younger generation is faced with a paradoxical condition. His high political awareness and participation contradict his political behavior which shows skepticism and apathy towards parliament and political parties that are supposed to accommodate his aspirations. They are often trapped in the echo chambers or social media algorithms that polarize so that it is easy to attack someone's personality in an uncivilized way. It's easy to throw hate speech on various social media platforms without first thinking about the impact it will cause. SDGs-based Civic Education Learning is an ethical basis towards political civility, but this seems to be still at the conceptual level. It has not been really implemented. The purpose of this study is to formulate and analyze a PKn learning model based on SDGs, especially SDG 16 to realize the political civility of young citizens. The research uses a qualitative research model with a classroom action approach that is carried out in a collaborative, participatory manner. Data was obtained from the results of participant observation and document analysis. The results of the study show that the learning of the Civic-Action Learning model in SDGs-based Civic Education learning can produce students who are able to analyze every event based on data and facts, show empathy, tolerance and high social concern, and be active in every real civic action.